A chimeric α-amylase engineered from Bacillus acidicola and Geobacillus thermoleovorans with improved thermostability and catalytic efficiency. (1st April 2016) - Parashar, Deepak; Satyanarayana, T
Abstract: The α-amylase (Ba-amy) of Bacillus acidicola was fused with DNA fragments encoding partial N- and C-terminal region of thermostable α-amylase gene of Geobacillus thermoleovorans ( Gt - amy ). The chimeric enzyme (Ba-Gt-amy) expressed in Escherichia coli displays marked increase in catalytic efficiency [ K  cat : 4 × 10 4  s −1 and K  cat / K  m : 5 × 10 4  mL −1  mg −1  s −1 ] and higher thermostability than Ba-amy. The melting temperature ( T  m ) of Ba-Gt-amy (73.8 °C) is also higher than Ba-amy (62 °C), and the CD spectrum analysis revealed the stability of the former, despite minor alteration in secondary structure. Langmuir–Hinshelwood kinetic analysis suggests that the adsorption of Ba-Gt-amy onto raw starch is more favourable than Ba-amy. Ba-Gt-amy is thus a suitable biocatalyst for raw starch saccharification at sub-gelatinization temperatures because of its acid stability, thermostability and Ca 2+ independence, and better than the other known bacterial acidic α-amylases.